Living the Faith : A Life of Tom Monaghan - Leonard, James, 1954- (Book collections on Project MUSE., 2012)
" Who is Tom Monaghan? Is he the four-year-old kid whose father died on Christmas Eve and whose mother sent him to an orphanage and then a juvenile detention home? Is he the entrepreneurial genius who built Domino's Pizza from a hole-in-the-wall pizzeria in Michigan into an American brand as world-conquering as Ford or Coke? Is he the religious visionary who sold Domino's for $1 billion to create an orthodox Catholic university, law school, and special interest law firm with the goal of transforming America to reflect his conservative values? He's all that and more. With extensive interviews with friends and enemies plus unprecedented access to the man himself, but wholly without his authorization, Living the Faith illuminates Tom Monaghan, the man and the myth. Living the Faith is the much-needed, definitive biography of one of America's most fascinating and controversial business and religious figures. A sympathetic but critical portrait of the man and his works, this book is for believers, nonbelievers, and agnostics; for conservatives, liberals, and independents; for the rich, the poor, and the shrinking middle class. Mainly, however, this book is for those who want the facts about Tom Monaghan--and the truth about the effect religion had on one man and the effect that man had on the world"--